A new source of autograft bone for interbody fusion in anterior cervical discectomy and fusion surgery: experience in 893 cases. (2nd January 2017) - Dang, Lei; Sun, Yu; Wang, Shaobo; Pan, Shengfa; Li, Mai; Zhang, Li; Zhang, Fengshan
Abstract: Purpose: This study is to share our experience of a modified anterior cervical discectomy and fusion (ACDF) procedure with a new source of autograft bone for interbody fusion. Methods: The same procedure was performed in 893 cases where autograft was obtained from the osteophytes and/or the reams of vertebrae. For each case, radiological fusion rate and clinical outcome were followed up for 3 and 12 months after surgery. Results: For one to three-level ACDF, fusion rates were from 67.8% to 75.4% at 3 months follow-up, and 92% to 98.8% at 12 months follow-up. Patients' VAS, NDI, JOA and SF-36 score improve significantly at 12 months follow-up. Conclusion: Osteophytes and vertebral reams can be a reliable source of bone graft that leads to high fusion rate and successful clinical outcome while avoiding all the problems with the current bone grafting methods used in ACDF surgery.